The Diffusion of Evidence-Based Decision Making Among Local Health Department Practitioners in the United States. Issue 2 (March 2015) - Harris, Jenine K.; Erwin, Paul C.; Smith, Carson; Brownson, Ross C.
<x xml:space="preserve">Abstract</x> Objectives: Evidence-based decision making (EBDM) is the process, in local health departments (LHDs) and other settings, of translating the best available scientific evidence into practice. Local health departments are more likely to be successful if they use evidence-based strategies. However, EBDM and use of evidence-based strategies by LHDs are not widespread. Drawing on diffusion of innovations theory, we sought to understand how LHD directors and program managers perceive the relative advantage, compatibility, simplicity, and testability of EBDM. Design, Setting, and Participants: Directors and managers of programs in chronic disease, environmental health, and infectious disease from LHDs nationwide completed a survey including demographic information and questions about diffusion attributes (advantage, compatibility, simplicity, and testability) related to EBDM. Bivariate inferential tests were used to compare responses between directors and managers and to examine associations between participant characteristics and diffusion attributes. Results: Relative advantage and compatibility scores were high for directors and managers, whereas simplicity and testability scores were lower. Although health department directors and managers of programs in chronic disease generally had higher scores than other groups, there were few significant or large differences between directors and managers across the diffusion attributes. Larger jurisdiction population size was associated with higher relative advantage and compatibility scores for both directors and managers. Conclusions: Overall, directors and managers were in strong agreement on the relative advantage of an LHD using EBDM, with directors in stronger agreement than managers. Perceived relative advantage has been demonstrated to be the most important factor in the rate of innovation adoption, suggesting an opportunity for directors to speed EBDM adoption. However, lower average scores across all groups for simplicity and testability may be hindering EBDM adoption. Recommended strategies for increasing perceived EBDM simplicity and testability are provided.